Financial Determinants of Foreign Direct Investment - Jens Forssbæk; Lars Oxelheim (Research Institute of Industrial Economics (IFN), 2008)
We argue that mainstream FDI theory underplays financial motivations for interna-tional investment, and suggest several possible channels for a distinct cost-of-capital effect on FDI. Using a sample of European firms cross-border acquisitions, and controlling for traditional firm-level determinants of FDI, we find strong evidence in favor of a cost-of-equity effect, whereas the effect of debt costs is indeterminate. We further find that financial determinants are more important for firms originating in relatively less financially developed countries and for firms with high knowledge intensity.
Keywords: E22; F21; F23; G30; L23; 330; FDI; Cross-border Acquisitions; Investment-q; Cost of Capital; Cross-listing; Segmentation; Direktinvestition; Übernahme; Multinationales Unternehmen; Kapitalkosten; Zweitlisting; Finanzmarkt; EU-Staaten